Structural Loads Survey During Cold-Weather Operations. - Cox,Terry L.; Torres,Thomas A. (1975)
To determine the effects of cold weather on the loads of dynamic components in the main and tail rotor systems of the UH-1H helicopter was the prime objective of the reported study. Accordingly, 18 hours of in-flight oscillograph data were recroded on these components while the helicopter flew at prescribed temperature-density altitude conditions in the arctic environment of Allen Army Airfield, Fort Greely, Alaska, during January and February of 1974. Equipped with strain gages, the instrumented components were the main and tail rotor blades, drag brace, scissors link, collective and cyclic boost tubes, and tail rotor shaft.